2005
DOI: 10.2174/156800905774574002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Invasion Induction as a Therapeutic Strategy for the Treatment of Cancer

Abstract: The spread of cancer cells from the primary tumor to a distant site involves many of the invasive processes normally required for wound healing, including migration through the local connective tissue, invasion of the vasculature, extravasation, invasion of the connective tissue at a distant site, and angiogenesis. Thus, the abilities of tumor cells to invade the host, and to induce endothelial cell invasion and neovascularization, are central to malignant progression. The plasminogen activator system, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 130 publications
0
20
0
Order By: Relevance
“…The a 5 h 1 integrin interacts with the PHSRN sequence of fibronectin cell-binding domain fragments to stimulate invasion during wound healing (2). Because epithelial cells, fibroblasts, and endothelial cells express the invasion-inhibitory a 4 h 1 integrin as well as a 5 h 1 , fibronectin fragmentation is required for invasion induction (3). Integrins are also very important in cancer progression (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The a 5 h 1 integrin interacts with the PHSRN sequence of fibronectin cell-binding domain fragments to stimulate invasion during wound healing (2). Because epithelial cells, fibroblasts, and endothelial cells express the invasion-inhibitory a 4 h 1 integrin as well as a 5 h 1 , fibronectin fragmentation is required for invasion induction (3). Integrins are also very important in cancer progression (4).…”
Section: Introductionmentioning
confidence: 99%
“…18), thereby bringing the catalytic subunit of PI3K to the membrane, where it catalyzes phosphorylation of inositol lipids at the D-3 position to form 3 ¶-phosphorylated phosphoinositides, including phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ). Integrin activation-induced FAK/PI3K association has been shown in both platelets and fibroblasts (19).…”
Section: Introductionmentioning
confidence: 99%
“…[20] Briefly, titanium (40 ) and gold (220 ) were evaporated onto glass coverslips using an electron beam evaporator (Thermionics) at a rate of 0.2-0.4 nm s À1 with a pressure of 1.0 10 À6 Torr. Monolayers were formed by immersing these substrates into an ethanolic solution containing a mixture of a symmetric tri(ethylene glycol)-terminated disulfide (EG 3 ) and an asymmetric disulfide with tri(ethylene glycol) and maleimide head groups for 12-16 h at room temperature . The disulfide reagents were used at a concentration of 0.5 mm with the maleimide-terminated group present at relative fractions of 1 % on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…[9,10] These compounds, at micromolar concentrations, were shown to block cell migration, but recent work reported that lower concentrations of these drugs can actually enhance the growth of tumors in vivo by promoting migration and VEGF-mediated angiogenesis. [7] Other recent work has investigated the analogy between tumor angiogenesis and wound healing [3,11] with the finding that the fibronectin-derived Pro-His-SerArg-Asn (PHSRN) peptide can stimulate migration of human kerotinocytes and fibroblasts and accelerate wound healing in obese diabetic mice. [8] Our group [12,13] and others [14] have suggested that PHSRN antagonizes RGD binding, and therefore may accelerate migration by inhibiting the integrinmediated adhesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation